Time to first positive HIV-1 DNA PCR may differ with antiretroviral regimen in infants infected with non-B subtype HIV-1. (28th November 2017) - Balasubramanian, Raji; Fowler, Mary Glenn; Dominguez, Kenneth; Lockman, Shahin; Tookey, Pat A.; Huong, Nicole Ngo Giang; Nesheim, Steven; Hughes, Michael D.; Lallemant, Marc; Tosswill, Jennifer; Shaffer, Nathan; Sherman, Gayle; et al.
Abstract : Objective: To evaluate the association of type and timing of prophylactic maternal and infant antiretroviral regimen with time to first positive HIV-1 DNA PCR test, in nonbreastfed HIV-infected infants, from populations infected predominantly with HIV-1 non-B subtype virus. Design: Analysis of combined data on nonbreastfed HIV-infected infants from prospective cohorts in Botswana, Thailand, and the United Kingdom ( N = 405). Methods: Parametric models appropriate for interval-censored outcomes estimated the time to first positive PCR according to maternal or infant antiretroviral regimen category and timing of maternal antiretroviral initiation, with adjustment for covariates. Results: Maternal antiretroviral regimens included: no antiretrovirals ( n = 138), single-nucleoside analog reverse transcriptase inhibitor ( n = 165), single-dose nevirapine with zidovudine ( n = 66), and combination prophylaxis with 3 or more antiretrovirals [combination antiretroviral therapy (cART), n = 36]. Type of maternal/infant antiretroviral regimen and timing of maternal antiretroviral initiation were each significantly associated with time to first positive PCR (multivariate P < 0.0001). The probability of a positive test with no antiretrovirals compared with the other regimen/timing groups was significantly lower at 1 day after birth, but did not differ significantly after age 14 days. In a subgroup of 143 infants testing negative at birth, infant cART was significantly associated with longer time to first positive test (multivariate P = 0.04). Conclusion: Time to first positive HIV-1 DNA PCR in HIV-1-infected nonbreastfed infants (non-B HIV subtype) may differ according to maternal/infant antiretroviral regimen and may be longer with infant cART, which may have implications for scheduling infant HIV PCR-diagnostic testing and confirming final infant HIV status. Abstract : Supplemental Digital Content is available in the text